Pembuatan Game 2D Materi Bangun Datar Menggunakan Metode ADDIE - Revika Aprillya, Zefanya; Andriyanto, Sidhiq; Pratiwi, Indah Riezky (Jurnal Inovasi Teknologi Terapan, 2025)
Educational games are games that contain learning content, including Mathematics learning. The Mathematics educational game development project aims to improve the ability of junior high school students in grade VII to understand basic Mathematics concepts in the field of Planar Buildings by incorporating Mathematics learning materials into educational games of the RPG (Role Playing Game) type. The research method used in this study is Research and Development, with the ADDIE development model. This development process includes several main stages, namely analyzing student needs by conducting interviews with grade VII Mathematics subject teachers, designing prototypes or game flows, developing educational game applications using Construct 2, testing involving material experts, and media, and direct testing on grade VII junior high school students. The validation results from material experts reached 84% and media expert validation reached 90% with valid criteria. Application testing with Black Box Testing on grade VII students of SMP Negeri 2 Sungailiat obtained an effectiveness level of 91.6%. Thus, the Datar Building educational game for grade VII junior high school students is declared valid and feasible.